1997
DOI: 10.1002/macp.1997.021980416
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic polymers obtained by precipitation polycondensation, 2. Synthesis of poly(ether ketone ether ketone ketone) (PEKEKK)

Abstract: A high molecular weight, linear aromatic poly(ether ketone ether ketone ketone) (PEKEKK) has been synthesized by electrophilic Friedel-Crafts acylation condensation of 1,4-diphenoxybenzophenone with terephthaloyl chloride. The syntheses were performed as precipitation polycondensations, and the polyketones were obtained in particle form. The viscosity (molecular weight), shape and size of these particles were found to be strongly dependent on the reaction conditions. For low monomer concentration, highly order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…7 The inherent viscosity of the polymer used is 0.96 dL/g (measured at 25°C on a 0.1% solution of the polymer in 98% sulfuric acid). The transparent amorphous glassy film was obtained by quenching the hot-press sheets in ice water from the melt (420°C).…”
Section: Materials and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The inherent viscosity of the polymer used is 0.96 dL/g (measured at 25°C on a 0.1% solution of the polymer in 98% sulfuric acid). The transparent amorphous glassy film was obtained by quenching the hot-press sheets in ice water from the melt (420°C).…”
Section: Materials and Preparationmentioning
confidence: 99%
“…Up to now, only relatively few articles have reported on this polymer, mainly on its synthesis, 7 crystal structure, 8 polymorphism, 9 and crystallization behavior. 10 Practical processes such as extrusion, molding, and film production are usually performed under dynamic, nonisothermal conditions, so it is of great practical significance to study the nonisothermal crystallization process quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Although the C = O stretching band of ketone group and the C‐O stretching band of ether group were observed at 1642 cm −1 and about 1260 cm −1 in both spectra of soluble and insoluble parts in sulfuric acid, the O‐H stretching band of hydroxyl group was clearly observed at about 3200 cm −1 in the spectrum of insoluble parts. Several side reactions for the nucleophilic aromatic substitution reactions are well known . For instance, the phenoxide abstract a proton from a halide‐activated aromatic ring to give a carbanion and a phenol residue, and the carbanion reacts continuously with carbonyl group or aromatic rings .…”
Section: Resultsmentioning
confidence: 99%
“…Preparations of PEKs are classified into two methods; the aromatic nucleophilic substitution and the aromatic electrophilic substitution, so-called Friedel-Crafts acylation catalyzed by aluminum trichloride (AlCl 3 ) [1]. In the latter case, the reaction gives a precipitate of the complex of oligomer and catalyst in the course of polymerization [2][3][4][5][6]. It has been revealed that even though the oligomer is precipitated, the molecular weight of PEK increases with reaction time in the precipitates formed in 1,2-dichloroethane (DCE) [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, the reaction gives a precipitate of the complex of oligomer and catalyst in the course of polymerization [2][3][4][5][6]. It has been revealed that even though the oligomer is precipitated, the molecular weight of PEK increases with reaction time in the precipitates formed in 1,2-dichloroethane (DCE) [3,5,7]. Since it is generally thought that precipitation terminates chain growth, the increase of molecular weight after precipitation is very interesting phenomenon.…”
Section: Introductionmentioning
confidence: 99%